Pengaruh Keterlibatan Fashion, Konsumsi Hedonis, dan Visual Merchandising Terhadap Pembelian Impulsif dengan Emosi Positif Sebagai Variabel Mediasi - Alifatuzzahra, Ashita; Rimiyati , Hasnah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
This study aims to analyze the effect of fahion involvement, hedonic consumtion, visual merchandising on impulse buying with positive emotion as mediation variables. Exogenous variables in this study are fashion involvement, hedonic consumtion, and visual merchandising, with impulse buying as an endogenous variable and positive emotion as an intervening variable. The object of this research is Uniqlo Hartono Mall fashion retail with total sample 168 respondents. The data analysis technique in this study used Structural Equation Modeling (SEM) with analysis tool that is AMOS 22 software. Based on the research indicate that fashion involvement has a significant effect on positive emotion, hedonic consumption has a significant effect on positive emotion, visual merchandising has a significant effect on positive emotion, positive emotion has a significant effect on impulse buying, fashion involvement has a significant effect on impulse buying, hedonic consumption has a significant effect on impulse buying, visual merchandising has a significant effect on impulse buying, positive emotion capable to mediate the influence of fashion involvement on impulse buying, positive emotion able to mediate the influence of hedonic consumtion on impulse buying, and positive emotion able to mediate the visual merchandising on impulse buying.